Current Collegiate Experiences of Big-Time, Non-Revenue, NCAA Athletes - Amanda L. Paule; Todd A. Gilson (University of Kansas Libraries, 2010)
Over the past 30 years experiences of collegiate athletes have been a major focus of scholarly research. Through well-known works, student-athletes' roles and personal development have been cornerstones of this new knowledge base (Adler & Adler, 1991; Lapchick, 1987). However, an understanding of the big-time athlete who also participates in nonrevenue sports1 is grossly under-represented in the literature. Thus, the purpose of this study was to examine the benefits and challenges that athletes in these sports (e.g., tennis, soccer, golf, track and field, etc.) currently experience. Interviews were conducted with 30 collegiate athletes-who were chosen at random from a sample pool of 9,231 athletes around the country-that focused on the types of benefits and the specific challenges that these athletes face while attending college. Results revealed current benefits of being a big-time, nonrevenue college athlete were very heterogeneous with a total of 24 distinct themes mentioned. The most popular of these included: academic benefits, being on a team, learning life skills, improved time management, and tangible benefits such as equipment, facilities, scholarship and travel. Current challenges that athletes face were much more homogenous, as only three lower order themes received more than two responses: missing out on things in college, lack of free time, and being stereotyped. As a whole, most athletes believed the challenges they face were worth the perceived benefits; and thus, big-time, non-revenue athletes do not receive an inferior overall college education experience (Potuto & O'Hanlon, 2007).